NGS plus bacterial culture: A more accurate method for diagnosing forensic-related nosocomial infections. (September 2021) - Yu, Zhonghao; Xie, Qiqian; Zhao, Yifeng; Duan, Lizhong; Qiu, Pingming; Fan, Haoliang
Highlights: We proposed an NGS-based method, 16S rDNA sequencing plus bacterial culture. The method can diagnose forensic-related nosocomial infections more accurately. The CT artifacts indicated we should be cautious when conducting virtual anatomy. Abstract: Traditional autopsy and microscopic examination of pathological sections are the "gold standard" for the cause of death diagnosis. However, in some special cases, such as the deaths caused by bacterial infections, pathological sections are not always sufficient to provide convincing evidences for determining the causes of death. In recent years, with the development of Next Generation Sequencing (NGS), clinical medicine has already introduced it into the diagnosis of difficult diseases, which is rare in forensic pathological diagnoses. Here, we applied an NGS-based method combined with bacterial culture to examine a special case in which the deceased was suspected of having suffered from nosocomial infections. Results of the NGS and bacterial culture showed that Enterococcus and Acinetobacter baumannii, which are the most common bacteria causing nosocomial infections, were abundant in blood and hydropericardium of the deceased. Combining medical records and the results of the dissections, we proved that the death was actually caused by MODS which was the adverse consequence of nosocomial infections. In this case, the combination of NGS and bacterial culture was used to identify the pathogen which had caused the death. The results of NGS not only shorten the period of diagnosis, but also greatly increase the credibility of traditional anatomy and results of bacterial culture, which is expected to be further applied for forensic practices in the near future.